Blue light irradiation increases the relative abundance of the diatom Nitzschia palea in co‐culture with cyanobacterium Microcystis aeruginosa. (10th April 2022) - Watanabe, Shunsuke; Matsunami, Naoki; Okuma, Ikki; Naythen, Podiapen Tannen; Fujibayashi, Megumu; Iseri, Yasushi; Hao, Aimin; Kuba, Takahiro
Abstract: Lake eutrophication is associated with cyanobacterial blooms. The pennate diatom Nitzschia palea ( N. palea ) inhibits the growth of the cyanobacterium Microcystis aeruginosa ( M. aeruginosa ); therefore, increasing the relative abundance of N. palea may contribute to the inhibition of Microcystis blooms. Several studies have demonstrated that blue light irradiation promotes diatom growth and inhibits cyanobacterial growth. In this study, we evaluated the effects of blue light irradiation on N. palea and M. aeruginosa abundance. Monocultures and co‐cultures of N. palea and M. aeruginosa were exposed to blue light and fluorescent light at 32 μmol photons m −2 s −1 . The relative abundance of N. palea under fluorescent light decreased gradually, whereas the abundance under blue light was relatively higher (approximately 74% and 98% under fluorescent light and blue light, respectively, at the end of the experiment). The inhibition efficiency of blue light on the growth rate of M. aeruginosa was related to the light intensity. The optimal light intensity was considered 20 μmol photons m −2 s −1 based on the inhibition efficiency of 100%. Blue light irradiation can be used to increase the abundance of N. palea to control Microcystis blooms. Practitioner Points: The effects of blue light irradiation on N. palea abundance was discussed. Monocultures and co‐cultures of N. palea and M. aeruginosa were exposed to blue light and to fluorescent light. The relative abundance of N. palea increased upon irradiation with blue light in co‐culture with M. aeruginosa . Abstract : In this study, we evaluated the effects of blue light irradiation on Nitzschia palea and Microcystis aeruginosa abundance. Monocultures and co‐cultures of N. palea and M. aeruginosa were exposed to blue light and fluorescent light at 32 μmol photons m−2 s −1 . The relative abundance of N. palea under fluorescent light decreased gradually, whereas the abundance under blue light was relatively higher (approximately 74% and 98% under fluorescent light and blue light, respectively, at the end of the experiment).